2005
DOI: 10.1002/uog.2025
|View full text |Cite
|
Sign up to set email alerts
|

OC5.05: Changes in fetal cardiac geometry with gestation: implications for three‐dimensional fetal echocardiography

Abstract: Extensive 1st trimester nuchal translucency (NT) evaluation arises the need for early diagnosis of major CHD and genetic counselling in cases with increased NT and normal kariotype. Our group organized a collaborative multidisciplinary study to offer early echocardiography. Our aim was to verify if precocious transabdominal echocardiography using high frequency probes is feasible and reliable in these pregnancies within 14 weeks of gestation (wg). Methods: 133 fetuses with increased NT (above 95th percentile) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…However, previous reports from us and others have shown how this condition can be easily met during a routine sonographic examination. 6,8,12,22 Moreover, maternal obesity and early or late gestational age can limit the possibility of obtaining such measurements. Indeed, in the first trimester, the reproducibility of volume measurements is poor because of the small volumes of the ventricles, 13 whereas in the late third trimester, the ossified ribs and their consequent shadows obscure accurate definitions of the limits of the ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports from us and others have shown how this condition can be easily met during a routine sonographic examination. 6,8,12,22 Moreover, maternal obesity and early or late gestational age can limit the possibility of obtaining such measurements. Indeed, in the first trimester, the reproducibility of volume measurements is poor because of the small volumes of the ventricles, 13 whereas in the late third trimester, the ossified ribs and their consequent shadows obscure accurate definitions of the limits of the ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the geometry of the heart and great vessels changes during gestation. The angles between the ductal arch and fetal thoracic aorta, the ductal arch and aortic arch, and the left outflow tract and main pulmonary artery all change throughout gestation and this may have ramifications for the geometrical assumptions used in volume calculations16.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this new method allowed measurement of the rotation angles from the four‐chamber view to the LVOT view in a reproducible manner. A similar study assessing angles between different cardiac structures through STIC has been described, which also demonstrated changes in cardiac geometry with advancing gestational age by measuring these angles14.…”
Section: Discussionmentioning
confidence: 83%
“…However, standardization of the method has not been described previously. Furthermore, a study investigating fetal cardiac geometry during pregnancy found that various angles changed with increasing gestational age and concluded that this may have implications for 3D and 4D algorithms proposed for fetal echocardiography14.…”
Section: Introductionmentioning
confidence: 99%